1984
DOI: 10.1254/jjp.35.181
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of in vitro neutrophil responses to chemotactic factors by piroxicam.

Abstract: Abstract-The effect of piroxicam on polymorphonuclear neutrophils (PMN) functions induced by several stimuli was evaluated in vitro. Preincubation of rabbit or human PMN with piroxicam inhibited the cellular responses elicited by N-formylmethionyl-leucyl-phenylalanine (FMLP) such as superoxide anion (O2-) generation, granule enzyme release and chemotaxis. The effectiveness of piroxicam on each response was superior to those of indomethacin and ibuprofen. Also when either concanavalin A, zymosan-treated serum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

1985
1985
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…TANAKA et al [23] described an inhibition of [3H]-fMLP binding to PMN but our observations obtained with two different chemoattractants led us to conclude to an interaction with at least two types of specific receptors and perhaps to a non specific modification of PMN membrane.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…TANAKA et al [23] described an inhibition of [3H]-fMLP binding to PMN but our observations obtained with two different chemoattractants led us to conclude to an interaction with at least two types of specific receptors and perhaps to a non specific modification of PMN membrane.…”
Section: Discussioncontrasting
confidence: 56%
“…An inhibition by piroxicam of rabbit PMN chemotaxis and O; generation induced by various stimuli (fMLP, concanavalin A, ionophore A 23187, activated serum) has already been described by TANAKA et al [23]. These authors suggest that the effect observed with 0 2 generation cannot be due to the interference of receptor-ligand binding but is likely to be due to the inhibition of an activation step of the 0 2 generating system of PMN common to all the stimuli used.…”
Section: Discussionmentioning
confidence: 72%
“…However, Tanaka et al (1984), using Boyden's chamber technique, showed that with 10 pmol L-I indomethacin (about 4 p g mL-l), chemotaxis in response to FMLP is inhibited by 19.6%. We found a 10.2% inhibition at this concentration, using the technique of migration under agarose gel.…”
Section: Discussionmentioning
confidence: 98%
“…We demonstrated in vivo that indomethacin inhibited the IL-8-induced infiltration of leukocytes. Indomethacin was also reported to inhibit adhesivity and chemotaxis of neutrophils in response to zymosan-activated serum or N-formyl-methionyl-leucyl-phenylalanine (FMLP) [26] and the release of lysosomal enzymes and the production of superoxide anions by neutrophils [27].…”
Section: Discussionmentioning
confidence: 99%